Association Between Smoking and Serum GlycA and High‐Sensitivity C‐Reactive Protein Levels: The Multi‐Ethnic Study of Atherosclerosis (MESA) and Brazilian Longitudinal Study of Adult Health (ELSA‐Brasil). Issue 8 (23rd August 2017) - Kianoush, Sina; Bittencourt, Marcio S.; Lotufo, Paulo A.; Bensenor, Isabela M.; Jones, Steven R.; DeFilippis, Andrew P.; Toth, Peter P.; Otvos, James D.; Tibuakuu, Martin; Hall, Michael E.; Harada, Paulo H. N.; Blaha, Michael J.
Abstract : Background: Inflammation is suggested to be a central feature of atherosclerosis, particularly among smokers. We studied whether inflammatory biomarkers GlycA and high‐sensitivity C‐reactive protein are associated with cigarette smoking. Methods and Results: A total of 11 509 participants, 6774 from the MESA (Multi‐Ethnic Study of Atherosclerosis) and 4735 from ELSA‐Brasil (The Brazilian Longitudinal Study of Adult Health) were included. We evaluated the cross‐sectional association between multiple measures of smoking behavior and the inflammatory biomarkers, GlycA and high‐sensitivity C‐reactive protein, using regression models adjusted for demographic, anthropometric, and clinical characteristics. Participants were 57.7±11.1 years old and 46.4% were men. Never, former, and current smokers comprised 51.7%, 34.0%, and 14.3% of the population, respectively. Multivariable‐adjusted mean absolute difference in GlycA levels (μmol/L) with 95% confidence interval (CI) were higher for former (4.1, 95% CI, 1.7–6.6 μmol/L) and current smokers (19.9, 95% CI, 16.6–23.2 μmol/L), compared with never smokers. Each 5‐unit increase in pack‐years of smoking was associated with higher GlycA levels among former (0.7, 95% CI, 0.3–1.1 μmol/L) and current smokers (1.6, 95% CI, 0.8–2.4 μmol/L). Among former smokers, each 5‐year increase in time since quitting smoking was associated with lower GlycA levels (−1.6, 95% CI, −2.4 to −0.8 μmol/L) and each 10‐unit increase in number of cigarettes/day was associated with higher GlycA among current smokers (2.8, 95% CI, 0.5–5.2 μmol/L). There were similar significant associations between all measures of smoking behavior, and both log‐transformed GlycA and high‐sensitivity C‐reactive protein. Conclusions: Acute and chronic exposure to tobacco smoking is associated with inflammation, as quantified by both GlycA and high‐sensitivity C‐reactive protein. These biomarkers may have utility for the study and regulation of novel and traditional tobacco products.